Duchowy niepokój, czyli o sumieniu słów kilka - Homa, Tomasz (Horyzonty Wychowania, 2017)
The concept of conscience is not an unambiguous term and is not infrequently exposed to the danger of reducing its characteristic depth. This danger appears especially where it is understood above all, or, in extreme cases, merely as man’s ability or his specific power involving pronouncing judgements on particular deeds or attitudes, in terms of moral good or evil, passing over, and sometimes even forgetting about what makes it capable, as well as the space in which this distinctive process takes place, thus constitutively belonging to the nature of this specific human reality. An opposed view of understanding of conscience as a judgement, the existentially experienced conscience perceived as distinctive spiritual space marked with the sense of humanness appears – with a privileged place for meetings and growth. Meetings with oneself, with another man and with God, as well as growing in freedom and love, towards complete humanness. What best characterises it is the experience and understanding that authentic self-fulfilment as a person – open with the Absolute, as well as with the whole reality – means our welfare and obligates. The emerging responsibility for oneself calls on to search for forms and ways, not just any, but harmonious with the discovered sense of one’s own existence, in order to accomplish this moral good. Whereas, the gradually emerging horizon of sense, constitutively contributing to man’s moral awareness, not only lightens self-understanding, but also makes us capable of appropriate grasping of the deepest essence of good or evil of our particular decisions. In this way, conscience becomes „the light”, „the guide” and „the judge” of our being, our self-fulfilment in freedom. Many a thing indicate that moral awareness and ability to pronounce specific judgements, though diverse in terms of proprium typical of each of them, indeed constitute one, dynamic and indivisible entity. Breaking it inevitably leads to limiting, and sometimes even distortion of one’s own humanness.